Systematic review of the psychometric properties of the Victorian Institute of Sports Assessment - Achilles tendinopathy questionnaire. - Ortega-Ávila, Ana Belén; Reina Martín, Inmaculada; Cervera-Garvi, Pablo; Lópezosa-Reca, Eva; Cabello-Manrique, David; Gijón-Noguerón, Gabriel (Taylor & Francis, 2019)
Objective: To review the different versions of The Victorian Institute of Sports Assessment - Achilles questionnaire for Achilles tendinopathy to evaluate its psychometric properties and the methodological quality of these studies. Methods: This study is a systematic review. Setting: A search was conducted in the PubMed, SCOPUS, CINAHL, Physiotherapy Evidence Database and Google Scholar databases, based on the following inclusion criteria: population with Achilles tendinopathy >18 years; validation studies of the Victorian Institute of Sports Assessment-Achilles questionnaire, in different languages, with no time limit. Two of the present authors independently assessed the quality of the studies located and extracted the relevant data. Terwee's criteria and the COSMIN checklist were employed to ensure adequate methodological quality. Results: Eleven instruments met the inclusion criteria for this review. Significant methodological flaws were detected, mostly regarding construct validity and responsiveness. Conclusions: The cultural adaptation of the Spanish-language and Brazilian-Portuguese-language VISA-A presents adequate methodological quality. However, further studies are required, with greater methodological rigor, of the cultural adaptations of measurement instruments.IMPLICATIONS FOR REHABILITATIONOn available evidence, the Spanish-language and Brazilian-Portuguese language versions of the Victorian Institute of Sports Assessment - Achilles questionnaire are the most appropriate for patients with Achilles tendinopathy.Robust methods should be designed and implemented to obtain higher quality instruments for patients with Achilles tendinopathy to be used systematically in daily clinical practice.Most previous transcultural versions of the Victorian Institute of Sports Assessment - Achilles tendinopathy questionnaire have presented inadequate evidence of their psychometric properties and should be used with caution for patients with Achilles tendinopathy.
https://v2.sherpa.ac.uk/id/publication/20617
Keywords: Psicometría; Aquiles, Tendón de; Tendones; Achilles tendon; VISA; Psychometrics; Systematic review; Tendinopathy